2016
DOI: 10.1212/wnl.0000000000003156
|View full text |Cite
|
Sign up to set email alerts
|

Early stridor onset and stridor treatment predict survival in 136 patients with MSA

Abstract: Our results demonstrated that early stridor onset is an independent predictor for shorter survival and that tracheostomy could control stridor, influencing disease duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 35 publications
2
50
0
Order By: Relevance
“…The prevalence of stridor in patients with MSA varies from 15% to 40% (Ghorayeb et al, 2002) and can, in some cases, be the presenting feature of the disease (Kaufmann et al, 2017a). Vocal cord paralysis and early stridor in patients with MSA are risk factors for shorter survival (Giannini et al, 2016; Lalich et al, 2014). Indirect laryngoscopy is useful in the diagnosis of stridor, and serial examinations may be required.…”
Section: Sleep Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of stridor in patients with MSA varies from 15% to 40% (Ghorayeb et al, 2002) and can, in some cases, be the presenting feature of the disease (Kaufmann et al, 2017a). Vocal cord paralysis and early stridor in patients with MSA are risk factors for shorter survival (Giannini et al, 2016; Lalich et al, 2014). Indirect laryngoscopy is useful in the diagnosis of stridor, and serial examinations may be required.…”
Section: Sleep Disordersmentioning
confidence: 99%
“…Stridor represents a life-threatening condition as it may lead to respiratory failure (Yamaguchi et al, 2003). It is unclear whether tracheostomy placement prolongs survival (Giannini et al, 2016). …”
Section: Sleep Disordersmentioning
confidence: 99%
“…Similarly, in patients with Parkinson's disease, the presence of OSAS was shown to be associated with worse cognitive functioning [19]. In patients with multiple system atrophy, the presence of stridor occurring early in the disease course was demonstrated as an independent predictor of a shorter survival [20], and SBD were suggested as a potential link to worse prognosis.…”
Section: Discussionmentioning
confidence: 98%
“…The discrepancy might have occurred because stridor is not assessed by clinicians but by caregivers without an objective tool such as video-polysomnography, in this study. A previous study demonstrated that 16.1% of patients presented stridor as an early (< 3 years) manifestation and early stridor onset is an independent risk factor for shorter survival in MSA patients [32]. Furthermore, it has been reported that stridor was an initial manifestation in 4-5.2% of patients with MSA [31].…”
Section: Discussionmentioning
confidence: 99%